Antimicrobial Resistance in Fecal Escherichia coli from Humans and Pigs at Farms at Different Levels of Intensification - Lunha, Kamonwan (Antibiotics (Basel), 2020)
The overall aim of the current study was to test the hypotheses that (i) antibiotic resistance in bacteria were more frequent in clinically health pigs in intensified company owned, medium-scale farms (MSFs) (100–500 sows) than in pigs in family-owned, small-scale farms (SSFs) (1–50 sows) and (ii) that farmers working at the MSFs were more prone to attain antibiotic resistant bacteria than farmers working at SSFs. The study was conducted in North-Eastern Thailand, comprising fecal Escherichia coli isolates from pigs, farmers working with the pigs (contact humans) and persons living in the same household as the farmer (non-contact humans) at 51 MSFs and 113 SSFs. Samples from all farms were also screened for methicillin-resistant staphylococcus aureus (MRSA), which was not detected in pig samples, but was found in one human sample. Susceptibility was tested by disc-diffusion for seven antibiotics commonly used in the study area. Resistance in pig isolates from MSFs were more frequent for chloramphenicol which (P < 0.001), trimethoprim/sulfamethoxazole (P < 0.001) and gentamicin (P < 0.05) compared with isolates from SSFs, whereas the opposite was true for tetracycline (P < 0.01). Resistance in the human isolates was lower than those in the isolates from pigs for tetracycline, trimethoprim/sulfamethoxazole and chloramphenicol (P < 0.001). The frequency of resistance in the contact human samples from SSFs and MSFs did not differ. There was no difference between isolates from contact and non-contact humans for any of the tested antibiotics. Multidrug resistance in isolates from pigs was 26%, significantly higher (P < 0.01) than the 13% from humans. The data indicate that (i) resistance to antibiotics, including those critical and highly important for human medicine, were more common in fecal E. coli from pigs at the MSFs than at the SSFs, whereas (ii) the resistance in fecal E. coli from pig farmers seemed not to be influenced by the level of intensification of the farm they were working at.